Sistema de comunicación a través de telefonía IP, basado en Elastix y Troncales tipo SIP, en la empresa IS Consulting - Guamán Guamán, Marco Bnejamín (2017)
In the company IS Consulting currently has a SIP line communication service through a pre-configured voice gateway which provides two fixed lines, through an analysis and study of it, it can be said that in the company there is Inefficiency in the telephone communication distribution process in its different departments, therefore it is intended to implement a communication system through IP telephony, based on Elastix and SIP-type trunks, with the aim of optimizing internal and external communication in IS Consulting company but, above all, guarantee a good service. For the execution of these activities, latest technology equipment will be used, which allow the communication through the use of VoIP (Voice over IP), and implementing SIP-type trunks, which will be distributed by a main server and with the help of software Elastix (VoIP server) which will control and ensure the use of information, this process will be based on a methodology that consist of seven sequential steps. They are: Collection of Information, Information Collection, Analysis of the existing environment, environment test Design, Information Collection, Analysis of the existing environment, environment test Design, Selection of hardware and software to be used, Implementation process, Testing process and finally the observations, which will help the proposed project development and culmination process. In the results section, an analysis of the current situation of the network infrastructure and the traditional telephony, its services and applications is carried out. It details the organization, location, existing personnel, types of connections, current equipment, number of users with extensions, current host type, and types of users to make calls, which gives us a more accurate view of the type of IP telephony network to be designed.